Two image encryption methods with hiding effect based on moiré pattern. (2016) - Gao, Qian; Han, Zhen; He, Yongzhong; Wang, Daoshun
In the existing methods of image encryption based on moiré phase modulation, the superposed moiré pattern can be reconstructed periodically, but the deformed layer leaks the profile of the secret image. In order to solve the problem of leaking secrets, some methods modify the reference layer to a periodic structure and gain hiding effect. However, the superposed moiré pattern loses the feature of periodic reconstructing. Some methods improve it by adding random noise but the noise appears in the moiré pattern and decreases the quality of the pattern. In this paper, two methods are proposed to cover the leaking problem. In the first proposed method, the deformed layer is scrambled with vertical lines of random length. In the second proposed method, grid is defined as basic structure and its count of black pixels in deformed layer is varied with cover image to hide the secret. Furthermore, we define average contrast to evaluate the quality of superposed moiré pattern. Compared with deformed layers in previous methods, the deformed layers generated by the proposed methods have hiding effect as well as they guarantee periodic reconstructing of moiré pattern without random noise.